Enhancing of Purchase Intention: The Role of Social Media Influencer and Brand Awareness - Ariyana Citra Dewi; Puspa Novitasari (Universitas Sahid Surakarta, 2023)
The changing consumption patterns of society need to be anticipated by businesses. The presence of social media can be utilized to boost sales. Companies need to build their corporate image through branding and marketing on social media. This can be achieved by partnering with social media influencers. This research aims to analyze the influence of social media influencers and brand awareness on purchase intention. The sample in this study consisted of 100 Scarlett Whitening consumers residing in Solo Raya, aged 15-35 years old, and actively using social media. Data were analyzed using the SPSS application. The research results indicate that social media influencers do not have a significant influence on purchase intention. However, brand awareness has a significant impact on purchase intention, meaning that the higher consumers' awareness of the brand, the greater their inclination to purchase the product. The research model indicates an adjusted R-Square value of 0.531, signifying that both social media influencer and brand awareness variables collectively contribute to a 53.1% influence on purchase intention.